Empathy in Chinese media communication: A review of theory and practise - Wang, Yanxue; Kadir, Shamsiah Binti Abd; Hassim, Nurzihan Binti (Edelweiss Applied Science and Technology, 2025)
This study explores the role of empathy in Chinese media communication, with an emphasis on how traditional cultural values and philosophies inform emotional expression in both traditional and digital media environments. The research employs a qualitative methodology, analyzing diverse case studies including television programs, public service campaigns, and social media interactions. It is framed within philosophical traditions such as Confucianism, Taoism, and Buddhism, which emphasize values like filial piety, social harmony, and the concept of “face” (mianzi). The study finds that traditional Chinese values encourage subtle, indirect expressions of empathy, while digital platforms—especially among younger users—foster more personal, direct, and emotionally open communication. This shift reflects broader societal changes and evolving audience expectations. Empathy is increasingly serving as a bridge between cultural heritage and modern communicative practices. It enables deeper audience engagement while reflecting the tension between tradition and modernity. Media professionals can leverage culturally informed empathetic strategies to craft impactful narratives, improve audience resonance, and address complex issues such as mental health, gender equality, and environmental sustainability in a more socially responsive manner.